Generation and application of two monoclonal antibodies targeting conserved linear epitopes in the NP protein of influenza A virus - Yu-hui ZHAO; Xia WEN; Qi-bing LI; Li JIANG; Guang-wen WANG; Li-bin LIANG; Xiu-rong WANG; Hua-lan CHEN; Cheng-jun LI (Journal of Integrative Agriculture, 2022)
Monoclonal antibodies (mAbs) are widely used in virus research and disease diagnosis. The nucleoprotein (NP) of influenza A virus (IAV) plays important roles in multiple stages of the virus life cycle. Therefore, generating conserved mAbs against NP and characterizing their properties will provide useful tools for IAV research. In this study, two mAbs against the NP protein, 10E9 and 3F3, were generated with recombinant truncated NP proteins (NP-1 and NP-2) as immunogens. The heavy-chain subclass of both 10E9 and 3F3 was determined to be IgG2α, and the light-chain type was κ. Truncation and site-specific mutation analyses showed that the epitopes of mAbs 10E9 and 3F3 were located in the N terminal 84–89 amino acids and the C terminal 320–324 amino acids of the NP protein, respectively. We found that mAbs 10E9 and 3F3 reacted well with the NP protein of H1–H15 subtypes of IAV. Both 10E9 and 3F3 can be used in immunoprecipitation assay, and 10E9 was also successfully applied in confocal microscopy. Furthermore, we found that the 10E9-recognized 84SAGKDP89 epitope and 3F3-recognized 320ENPAH324 epitope were highly conserved in NP among all avian and human IAVs. Thus, the two mAbs we developed could be used as powerful tools in the development of diagnostic methods of IAV, and also surely promote the basic research in understanding the replication mechanisms of IAV.